Family farming in Brazil and its labor risks: A preventionist approach (Research, Society and Development, 2023)
Agriculture plays a fundamental role in the Brazilian economy, being responsible for supplying the domestic and foreign markets. It is essential, being responsible for a large part of the food in the country and in the world. About exports, this sector connects with several countries around the world. Data from the Brazilian Institute of Geography and Statistics - IBGE (2017), in its last agricultural census, indicated that the equivalent of 3.9 million agricultural properties are classified as family farming, which represents 76.8% of a total of 5.073 million agricultural establishments. It can be said that the need to cultivate different crops represents a challenge for those directly or indirectly involved in the productive activity. This work aims to study a specific segment of agriculture, called family farming, in aspects related to accident prevention, as well as exposure to the main harmful agents (environmental risks) in this segment.